2022
DOI: 10.1136/bmjdrc-2022-002937
|View full text |Cite
|
Sign up to set email alerts
|

Transition from pediatric to adult care in type 1 diabetes mellitus: a longitudinal analysis of age at transfer and gap in care

Abstract: IntroductionAdolescents and young adults (AYAs) with type 1 diabetes (T1D) are at risk of suboptimal glycemic control and high acute care utilization. Little is known about the optimal age to transfer people with T1D to adult care, or time gap between completing pediatric care and beginning adult endocrinology care.Research design and methodsThis retrospective, longitudinal study examined the transition of AYAs with T1D who received endocrinology care within Duke University Health System. We used linear multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…2. Perceived Stress Scale (PSS-10): a 10-item questionnaire originally developed by Cohen et al [13] that is widely used to assess stress levels in young people and adults aged 12 years and older; it evaluates the degree to which an individual has perceived life as unpredictable, uncontrollable, and overloading over the previous month. 3. Satisfaction with Life Scale (SWLS) [14]: a measure of global life satisfaction; scores on the SWLS correlate moderately to highly with other measures of subjective well-being and correlate predictably with specific personality characteristics.…”
Section: Psychological Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Perceived Stress Scale (PSS-10): a 10-item questionnaire originally developed by Cohen et al [13] that is widely used to assess stress levels in young people and adults aged 12 years and older; it evaluates the degree to which an individual has perceived life as unpredictable, uncontrollable, and overloading over the previous month. 3. Satisfaction with Life Scale (SWLS) [14]: a measure of global life satisfaction; scores on the SWLS correlate moderately to highly with other measures of subjective well-being and correlate predictably with specific personality characteristics.…”
Section: Psychological Questionnairesmentioning
confidence: 99%
“…These changes also concern diabetes; patients have to confront with the need to become responsible for various decisions and duties that so far were more caregiver based. It is necessary to undertake the responsibility for everyday management of diabetes-both emotional and clinical, which may be overwhelming, especially for young people whose parents were either overprotective or not engaged, which is a common issue in families with a child with chronic disease [2][3][4]. The results of the SEARCH for Diabetes in Youth Study [5] indicated a 2.5-fold increase in the risk of deterioration of metabolic control in a young adult cohort with T1DM leaving pediatric care compared to those under the care of pediatric clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinics in LRS transition at age 12 years while most transition between ages 15 and 21 years. There are numerous reports from around the world in high, middle and low resource settings that document the deterioration of glycemic control associated with increased acute and chronic morbidities in the PwD in the adolescent and young adult years, 86 and efforts to address these problems continue. Being aware of these difficulties, having honest discussions with the PwD and family and having joint programs for a few years between pediatricians and adult physicians has been helpful in raising awareness and addressing these issues.…”
Section: Transitionmentioning
confidence: 99%